ІСТОРИКО-ПЕДАГОГІЧНІ ПЕРЕДУМОВИ РОЗВИТКУ ПРОФІЛЬНОГО НАВЧАННЯ (Педагогіка вищої та середньої школи, 2008)
The article deals with retrospective analysis of profde differentiation’s problem. There is reveals the historico-pedagogical prerequisites for development and formation of profde education.